Decision Making in Social Context in Patients with Suicide Attempt History. Issue 5 (6th March 2016) - Sánchez‐Loyo, Luis; Ventura‐Martínez, Eva; González‐Garrido, Andrés Antonio
Abstract : Decision making has been found to be altered in suicide attempters, but little is known of their performance in social contexts. Twenty‐seven depressed suicide attempters (DSA), 25 nonsuicidal depressed patients (DP), and 60 healthy participants (HC) were evaluated by a decision‐making task in social context. Results indicated DSA and DP obtained lower gains and invested more money with angry partners. DSA were found to invest less money than DP and HC with happy partners. DSA showed insensitivity toward rewards/punishment contingency, and they did not use the socioemotional stimuli to guide their decisions.